Higher Capacity, Improved Conductive Matrix VB2/Air Batteries. Issue 5 (1st January 2016) - Lefler, Matthew; Stuart, Jessica; Parkey, Jeff; Licht, Stuart
Abstract : Transition metal borides, such as VB2, have been investigated as alternative, higher capacity anode materials. The VB2 high capacity is due to the capability to undergo a 4060 mAh/g formula weight multiple electron (11 e − ) alkaline oxidative discharge at a singular discharge potential plateau. With a comparable formula weight (10% higher) to zinc, VB2 has an intrinsic gravimetric capacity five fold higher than the 2 e − oxidation of the widely used zinc alkaline anode. One challenge to the implementation of VB2 /air batteries is that resistive oxide products impede the discharge depth, and only thin anode batteries (for example 10 mAh in a 1 cm diameter cell) had been demonstrated to discharge effectively. This study demonstrates that (i) smaller particle size (nano-VB2, as opposed to macroscopic VB2 ) helps to alleviate this effect and (ii) a stacked anode compartment configurations improve the anode conductive matrix significantly, resulting in an increase in the coulombic efficiency of high capacity, thicker anodes in VB2 /air batteries. Combined, these effects provide a 50% relative increase in the coulombic efficiency (from 50% to 75% at an 0.4 V discharge cutoff) of a 30 mAh coin cell, and increase the coulombic efficiency of the 100 mAh cell to 50%.